Factors Affecting on Adoption of Sustainable Agricultural Practices in Manipur - Thangjam, Bidyapati; Jha, K K; Sharma, Saurabh; Singh, Herojit (Indian Journal of Extension Education, 2024)
Adoption of sustainable practices in agriculture is crucial for ensuring the long-term viability of farming systems, protecting the environment, and promoting food security and economic prosperity for future generations. If the sustainable practices are not aligned with farmers’ needs, adoption status may likely to be low. To investigate the adoption behavior of farmers in the different dimensions of sustainable practices, a study was conducted in Manipur during November 2021 to July 2023. The data was gathered from randomly selected 320 respondents. The findings highlighted that the highest adopted sustainable agricultural practices was MW (manual weeding) and CR (crop rotation). Most of the respondents belonged to the medium level of adoption with a 51.53 adoption index. Using binary logistic regression, the effect of independent variables on the adoption of sustainable agricultural practices was tested. The model exhibits below moderate relationships, predicting 25.00 per cent of decisions to adopt sustainable agricultural practices, which can be explained by the independent variables. Furthermore, out of the eleven variables, seven variables were importantly influenced on the adoption of sustainable agricultural practices. Boosting farmers’ confidence through technology demonstration, awareness campaigns about the benefits of sustainable technology, and implementing a well-designed, user-friendly interface with feedback mechanisms can significantly enhance adoption rates.
Keywords: Sustainable agriculture; Technology adoption; Influencing factors and Manipur